Concepts of Mental Disorders Among Psychiatrists, Psychologists, and Theologians - Žana Kralj; Goran Kardum (MDPI AG, 2024)
The objective of this study was to compare the perspectives of psychiatrists, psychologists, and theologians on schizophrenia, depression, anxiety, and antisocial personality disorder. A cross-sectional research design was utilized, involving a random sample selected from the official registries of these professionals. The findings revealed significant differences in how these groups conceptualize mental disorders. The preferred concepts varied depending on the specific disorder. For instance, when it came to schizophrenia, psychiatrists showed a greater inclination towards the psychodynamic concept compared to psychologists, who leaned more towards the cognitive and social constructivist concepts. In the case of depression, psychiatrists favored biological, psychodynamic, and spiritual concepts, while psychologists tended to prefer the cognitive concept. Theologians consistently favored the spiritual concept across all four diagnoses, in comparison to both psychiatrists and psychologists. This research holds significant value for both theoretical understanding and practical applications, and future studies should consider incorporating qualitative, in-depth research to explore the complexities of these concepts related to mental disorders.